AlGaN/GaN High Electron Mobility Transistors with a p-Type GaN Cap Layer. (9th April 2018) - Tsai, Hsin-Chang; Fan Chiang, Shao-Chi; Zhong, Yi Nan; Hsin, Yue-Ming
Abstract : In this work, AlGaN/GaN HEMTs with different types of p-GaN cap layers were fabricated and investigated. The p-GaN cap layer used in this study was for passivation study instead of forming enhancement-mode operation. The differences in p-GaN cap layers were Mg-doping concentration (1×10 19 and 3×10 19 cm -3 ) and thickness (5 and 8 nm). Device with p-GaN cap of 8-nm and Mg-doping of 3×10 19 cm -3 showed the lowest gate leakage current, highest on/off current ratio (1.02×10 6 ), highest breakdown voltage and least current collapse characteristics.